Heart Rate Variability and Inflammatory Stress Response in Young African American Men: Implications for Cardiovascular Risk - Tell, Dina; Burr, Robert L.; Mathews, Herbert L.; Janusek, Linda Witek (Frontiers in Cardiovascular Medicine, 2021)
Abstract Background. African American men have a disproportionately higher incidence of and suffer greater severity and earlier death from cardiovascular disease (CVD). A common feature of many diseases, which disproportionately afflict disadvantaged African Americans, is inflammation. In particular, inflammation plays a decisive role in the pathogenesis of CVD in that persistent inflammation contributes to plaque evolution and destabilization. Adverse childhood experiences increase the risk for adult inflammatory based disease, particularly cardiovascular disease. This inflammatory burden becomes evident during stressful events and may be related to alterations in autonomic nervous system (ANS) activity. We previously reported that African American men who experienced childhood adversity exhibited a greater inflammatory (IL-6) response to acute stress challenge (Trier Social Stress Test – TSST). The purpose of this study was to determine whether altered ANS activity, as measured by heart rate variability (HRV), contributes to a greater proinflammatory response to stress in those exposed to childhood adversity. Methods. Thirty-four African American adult males underwent the TSST while instrumented with Holter monitors to record continuous heart rate for HRV determination. HRV was calculated as the low frequency (LF) to high frequency (HF) heart rate ratio (LF/HF), with higher LF/HF ratios corresponding to higher sympathetic versus parasympathetic activity. Salivary samples were collected pre- and post-TSST to measure the proinflammatory cytokine IL-6. Childhood adversity was assessed by the Childhood Trauma Questionnaire. Results. Hierarchical linear modeling demonstrated that higher levels of physical abuse were related to a steeper rise in LF/HF ratio during the TSST. Further, a higher LF/HF ratio, in combination with greater exposure to emotional and physical abuse was associated with a greater IL-6 response to the TSST. Conclusions. These findings suggest that adverse childhood experiences associate with an adult phenotype characterized by an altered ANS response to stress as well as a greater proinflammatory (IL-6) response to an acute stressor. Elevations in salivary inflammatory markers have been associated with increased CVD risk, including risk for atherosclerosis. In conclusion, these findings suggest a role for the ANS in the underlying neuro-biological processes whereby childhood adversity predisposes to a more intense inflammatory response to stressful challenge during adulthood.